Apamea permixta, sp. n., from China ?the putative sister species of A. commixta (Butler) (Lepidoptera, Noctuidae: Xyleninae: Apameini) - Kononenko, Vladimir (Zootaxa, 2006)
Apamea permixta, sp. n., is described from the Provinces of Fujan and Guandong, southeastern China. It appears to be the sister-species of the superficially similar A. commixta (Butler). It differs from the latter mainly in details of the structure of the male and female genitalia. The adult and male and female genitalia are illustrated, and a map of the distribution of both A. permixta and A. commixta is provided.